MAKNA KATA BERDAMAI DALAM FRASA “BERDAMAI DENGAN COVID” DI ERA NEW NORMAL - Mustikasari, Rizki; Wlandari, Rifa Suci; Harida, Ratri (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2020)
Meaning is the liaison of language with the outside world agreed by the speakers so that they can understand each other. On May 7, 2020 through the President's Presidential Secretariat YouTube channel, President Joko Widodo gave a speech on the implementation of the PSBB. In the speech, the President said